Hyperimmune globulin and monoclonal antibody for the treatment of SARS CoV-2 infection - Jesus Rodrigues da Motta, Oswaldo; Patricia Gomes, Andreia; Almeida de Oliveira, Leandro; de Almeida Oliveira, Leonardo; Henrique Santos Almeida, Caio; Muniz Braga, Luciene (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
The current pandemic of COVID-19 (Coronavirus Disease-19), caused by the pathogen SARSCoV-2, leading to thousands of deaths in 2020, has mobilized the scientific community, with the purpose of understanding the different aspects of the disease and proposing new treatment and prevention measures. Research carried out in several areas includes evaluating the possibility of using hyperimmune globulin and monoclonal antibodies against SARS CoV-2 as well as analyzing the viability and efficacy of monoclonal antibodies and hyperimmune globulin in combating Sars-CoV-2. A literature review was carried out with a defined search strategy using the keywords (i) “hyperimmune globulin”, (ii) “monoclonal antibody”, (iii)“ covid-19” and (iv)“ sars-cov-2”, in the PubMed and ResearchGate databases, using the bibliographic references of the articles selected in these databases. Of the 187 citations obtained, 10 articles published between 2019 and 2020 were selected after reading the summary of each one and determining its compatibility with the objective of this study. Final considerations highlight the main challenges and the feasibility of using hyperimmune globulin and monoclonal antibodies for the treatment/prevention of SARS CoV-2 infection. KEY WORDS: Hyperimmune globulin; monoclonal antibody; COVID-19; SARS-CoV-2.